"Eye genetics at the fork in the road" 2017 Franceschetti Lecture, Leeds UK. (3rd May 2020) - Mackey, David
ABSTRACT: Inherited retinal diseases – a disparate group of eye disorders with over 200 known genetic causes – are now the leading cause of blindness in working-age adults in developed countries. Until recently there was no cure for genetic eye diseases. After over a century of defining inherited retinal diseases with their phenotypes, and then several decades of discovering associated genes and their mutations, we now have gene therapy, stem cell therapy, predictive DNA testing and a revolution in adaptive computer technology. With the explosion of expensive treatment options, we need to consider whether finite resources should go towards treatment, prevention or rehabilitation or an amalgamation of all three. In addition, although evidence-based medicine is the goal, how do we direct our desperate patients towards genuine clinical trials and away from quackery? How do we provide scientifically valid treatments for eye diseases too rare to run proper trials and then capture the results of "off label treatments"?